Community integration of adults with disabilities post discharge from an in-patient rehabilitation unit in the Western Cape - Dietlind Gretschel; Surona Visagie; Gakeemah Inglis (AOSIS, 2017)
Introduction: Community integration is an important outcome of rehabilitation, because the ultimate focus of rehabilitation is to enable people to participate in their life roles. Aim: To determine community integration scores achieved by adults with disabilities post discharge from an in-patient rehabilitation centre in the Western Cape Province. Method: Fifty-nine individuals participated in this cross-sectional study. Community integration was determined using the Reintegration to Normal Living Index (RNLI). Descriptive analysis of age, gender, medical diagnosis and RNLI scores was performed. Kruskal-Wallis test and t-tests were used to determine whether there exists any relationship between age, gender, medical diagnosis and RNLI scores (p < 0.05). Results: Participants' mean age was 45 (± 15.9) years. Of the study participants, 54% were women. The most common diagnosis was stroke (41%), followed by spinal cord injury (30%). The mean overall RNLI score was 66.3 (± 25.5). Persons with brain trauma (stroke or head injury) had a mean of 60.9 (±20.3); those with spinal cord injury had a mean of 75.2 (± 25.8) and those with peripheral impairments had a mean of 65.5 (± 30.5). The RNLI domains 'personal relationships' 73.45 (± 31.6) and 'presentation of self' 72.13 (± 35.4) recorded the highest mean scores. The domain 'work or meaningful activities' had the lowest mean score 52.54 (± 35.3). 'Community mobility' (59.9; ± 34.6) and 'recreation' (57.3; ± 37.2) also had mean scores below 60. No statistically significant relationships were found between age, gender and medical diagnosis and RNLI scores. Conclusion: The relatively low mean scores indicate that participants achieved poor community reintegration.